Assessment of atopic dermatitis in all phototypes using line‐field confocal optical coherence tomography (LC‐OCT) and reflectance confocal microscopy (RCM) - Samantha Ouellette; Thu Minh Truong; Samavia Khan; Sara Ragi; Shazli Razi; Babar Rao (Wiley, 2024)
Abstract Background Theclinical presentation of atopic dermatitis (AD) varies in different skin phototypes and has been evaluated previously using reflectance confocal microscopy (RCM). Line‐field confocal optical coherence tomography (LC‐OCT) is a new noninvasive imaging modality with additional capabilities. Objectives This prospective cohort study aimed to assess the capabilities of LC‐OCT and RCM in visualizing and quantifying microscopic features of AD lesions. Methods Ten patients with clinically diagnosed AD and visible active lesions were included in the study. LC‐OCT and RCM imaging were performed on lesional and perilesional skin during routine dermatology visits. Image analysis included quantitative measurements of living and total epidermal thickness and dermo‐epidermal junction (DEJ) undulation using LC‐OCT, as well as visual assessment of characteristic features such as spongiosis, exocytosis, perivascular inflammation, and atypical blood vessels using both LC‐OCT and RCM. Results LC‐OCT provided precise measurements of epidermal landmarks and shared similar microscopic features compared to RCM. AD lesions exhibited increased stratum corneum thickness, living epidermis thickness, total epidermis thickness, and DEJ undulation compared to clinically normal skin. Spongiosis, exocytosis, perivascular inflammation, blood vessel proliferation, and dilation were prominent features observed in AD lesions on both LC‐OCT and RCM images. Interestingly, some inflammatory features were also detected in the visually normal skin of AD patients. Conclusions LC‐OCT showed potential as a fast and noninvasive imaging tool for assessing inflammatory skin pathologies, including AD. Its ability to visualize microscopic features and quantify epidermal changes may aid in diagnosis and treatment monitoring. These findings suggest that LC‐OCT could provide valuable insights, particularly for patients with darker skin types where clinical severity assessment may be challenging. Further studies are warranted to explore the full potential of LC‐OCT and its integration into clinical practice.